2010
DOI: 10.3238/arztebl.2010.0875
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Scoliosis

Abstract: Scoliosis is common. Early diagnosis makes a major difference in the choice of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
1
29

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(179 citation statements)
references
References 38 publications
2
133
1
29
Order By: Relevance
“…Another study comparing Endoret with controls for bilateral sinus floor augmentation in a series of five patients reported typical findings of 20-30% new bone formation in the treated area versus 8% new bone formation in the control area. Based on immunohistochemical analysis, the authors reported 116 blood vessels per mm (Trobisch et al 2010) in the treated area, compared with only 7 per mm (Trobisch et al 2010) in the control area (Anitua et al 2010b). …”
Section: Toward Clinical Impactmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study comparing Endoret with controls for bilateral sinus floor augmentation in a series of five patients reported typical findings of 20-30% new bone formation in the treated area versus 8% new bone formation in the control area. Based on immunohistochemical analysis, the authors reported 116 blood vessels per mm (Trobisch et al 2010) in the treated area, compared with only 7 per mm (Trobisch et al 2010) in the control area (Anitua et al 2010b). …”
Section: Toward Clinical Impactmentioning
confidence: 98%
“…During childhood and adolescence, deformities during skeletal growth can arise due to genetic defects, infectious disease, and other growth imbalances (Dixon et al 2011;Trobisch et al 2010). In adulthood, osteoarthritis and back pain are major contributors to immobility, pain, and lost productivity (Lories and Luyten 2011;Walker et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The AIS may resolve spontaneously, with growth, or may progress severely and even be associated with risk of mortality (1,15). The progressive deformity may cause several body prominences, asymmetric waistline, uneven shoulders, injured self-image, pain, spinal degenerative changes, limitations in activities of daily living and, in severe cases, disturbed pulmonary function (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis is a medical condition in which a person's spinal axis has a three-dimensional deviation [4]. It is typically classified as either congenital (15%) idiopathic (65%) or secondary (10%) to a primary condition.…”
Section: Scoliosismentioning
confidence: 99%